Gambaran Pemberian Infus Hangat Pada Pasien Shivering Pasca Spinal Anestesi di RSKD Ibu dan Anak Pertiwi Pemprov Sulawesi Selatan - Pasang, Michael; Yudono, Danang Tri; Yanti, Linda (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The use of warm liquids to prevent and treat the occurrence of shivering has been scientifically proven to be effective. The purpose of this study is to find out the overview of giving warm infusions to shivering patients after spinal anesthesia at the special regional hospital for Mother and Child of the South Sulawesi Provincial Government. First, the researcher collected data using an observation sheet. The next step, all the data obtained from the observation sheet is input in excel. The data input is in the form of data on age, gender, body temperature, BMI, type of warm infusion fluid, temperature of warm infusion fluid, and degree of shivering incidence. The results showed that: The characteristics of the respondents in this study were the age category in early adulthood (26-35 years) as many as 13 people (39.4%), the majority gender of women as many as 26 people (78.8%), the body temperature of patients in the hypotermic category as many as 21 people (63.6%) and the BMI of respondents in the normal category as many as 15 people (45.5%). The type of intravenous fluid used in post-spinal anesthesia shivering patients used crystalloid fluid as many as 25 people (75.8%). The temperature of warm infusion fluid in the mild warm temperature category (37 oC) was 19 people (57.6%). Patients experienced shivering events in grade 16 as many as 16 people (48.5%) and as many as 13 people (39.4%) experienced shivering events in grade 2.